Relationship Between Parental Practices and Aggressive Behavior in Adolescents from Aguascalientes, Aguascalientes - Doumerc Pompa, César Conrado (Consorcio de Universidades Mexicanas A.C., 2023)
Aggressive behavior represents one of the most relevant problems at present. Therefore, it is imperative to study its causes, processes, and consequences, as well as how it can be prevented and treated. One of the factors with which this behavior has been associated is parental practices. This study aimed to analyze practices of communication, autonomy, imposition, psychological control and behavioral control, and aggressive behavior in adolescents. A non-experimental, quantitative, cross-sectional and correlational study was carried out. Aggression Questionnaire and Parental Practices Scale were administered to a sample of 1,171 students between 15 and 19 years old (M=15.95), 53% of whom were female. Through Spearman’s Rho test, statistically significant correlations were found between the five dimensions of Parental Practices and the four of the Aggressive Behavior variables. Both parents' communication, autonomy and behavioral control were associated negatively, while imposition and psychological control did so positively. Rearing characterized by high levels of communication, promotion of autonomy, and adequate behavioral control, is associated with lower levels of aggressive behavior in adolescents.